Facile surface functional polyetheretherketone with antibacterial and immunoregulatory activities for enhanced regeneration toward bacterium-infected bone destruction - An'an Sun; Xi Lin; Zhiqiang Xue; Jiyue Huang; Xinxin Bai; Lingling Huang; Xinhua Lin; Shaohuang Weng; Min Chen (Taylor & Francis Group, 2021)
Existing biologically inert or unmodified implants to treat infectious bone defects or osteomyelitis still cannot effectively solve bacterial infection and osseointegration. In this work, a simple co-deposition strategy was developed to modify porous polyetheretherketone (PEEK) with improved antibacterial activity and controllable immunoregulatory ability. After PEEK was treated by H2SO4 to obtain porous PEEK (SPEEK), the self-polymerization of dopamine was operated on SPEEK in the solution of dopamine and gentamicin sulfate (GS) to prepare polydopamine (pDA) and GS layer-modified SPEEK (labeled as SPEEK-pDA-GS). The morphology, surface property, and molecular structure of SPEEK-pDA-GS were investigated. Besides the antibacterial property of SPEEK-pDA-GS ascribed to the successful immobilization of GS, SPEEK-pDA-GS exhibited promoted osseointegration through the results of mineralization, alkaline phosphatase (ALP) levels and osteogenic gene expression. Furthermore, the evaluation of the cell proliferation suggested that SPEEK-pDA-GS possessed the biocompatibility and the immunoregulatory ability that induced macrophages to anti-inflammatory M2 phenotype. Using rat as model, in vivo results containing X-ray, μ-CT, immunohistochemistry, and pathological analysis showed the excellent healing effect of SPEEK-pDA-GS on bone defect with infection with biological safety. This work illustrates a new insight into the simple and effective modification of PEEK and other implants with antibacterial, immunoregulatory, and osseointegration abilities for clinical requirement.